PENGARUH MONITORING RAKYAT PADA MEDIA SOSIAL TERHADAP PROSES PENEGAKAN HUKUM DI INDONESIA - Siti Mariyam; Adhi Putra Satria (UNES Law Review, 2023)
Democracy and Reform in Indonesia have had a significant impact on the people's participation and control over the nation's direction and development, one of which is the participation and control of the people in the formation and enforcement of the law. This study will attempt to provide an overview of the extent of public monitoring/control in law enforcement in Indonesia. The study is a normative juridical research, using secondary data as the main source, which is then analyzed qualitatively. The results show that public monitoring/control through social media in law enforcement in Indonesia has a great influence in determining the demands, defenses, and verdicts of individuals in legal cases. For example, in the case of Ferdy Sambo, the Indonesian people expressed their hopes on social media that Ferdy Sambo should be sentenced to death, although the prosecutor's office sentenced him to life imprisonment. However, the judge later gave Ferdy Sambo the death penalty in accordance with the aspirations of the Indonesian people. Nonetheless, comments and expressions of aspirations by the public through social media need to be regulated so as not to violate the rights of individuals who are involved in legal cases, including the right to be presumed innocent. Therefore, the government needs to develop and consider online petitions as a means for people to express their aspirations in an orderly and accountable manner.